2009
DOI: 10.1371/journal.pone.0007917
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Diabetes Mellitus Exacerbates Tau Pathology in a Transgenic Mouse Model of Alzheimer's Disease

Abstract: Diabetes mellitus (DM) is characterized by hyperglycemia caused by a lack of insulin, insulin resistance, or both. There is increasing evidence that insulin also plays a role in Alzheimer's disease (AD) as it is involved in the metabolism of β-amyloid (Aβ) and tau, two proteins that form Aβ plaques and neurofibrillary tangles (NFTs), respectively, the hallmark lesions in AD. Here, we examined the effects of experimental DM on a pre-existing tau pathology in the pR5 transgenic mouse strain that is characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
115
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 174 publications
(124 citation statements)
references
References 39 publications
7
115
1
1
Order By: Relevance
“…Decreased insulin signaling leaves cells vulnerable to oxidative stress and other metabolic insults and can increase inflammation and even tau phosphorylation (Bosco et al, 2011). Experimental diabetes mellitus exacerbates tau pathology in a transgenic mouse model of AD (Ke et al, 2009). The diabetes drug liraglutide has been shown to decrease neuropathology in a transgenic mouse model of AD (McClean et al, 2011), suggesting possible usefulness in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased insulin signaling leaves cells vulnerable to oxidative stress and other metabolic insults and can increase inflammation and even tau phosphorylation (Bosco et al, 2011). Experimental diabetes mellitus exacerbates tau pathology in a transgenic mouse model of AD (Ke et al, 2009). The diabetes drug liraglutide has been shown to decrease neuropathology in a transgenic mouse model of AD (McClean et al, 2011), suggesting possible usefulness in AD.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in insulin availability in the TG mice in this study may explain the increase in GLUT1. It has been found that depletion of insulin, which decreases HIF-1a, can induce hyperglycemic conditions in which blood glucose levels are increased (Ke et al 2009). Furthermore, conditions of hyperglycemia-induced insulin resistance can lead to enhanced glucose transport through insulin-independent GLUT1 and the hexosamine pathway, instead of through GLUT4 (Ebeling et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins were extracted according to solubility as described, using FA or sarkosyl (49,50). Western blotting was performed as described (51).…”
Section: Neuroscience Methodsmentioning
confidence: 99%